Batteux, Kant and Schiller on fine art and moral education. Issue 6 (3rd December 2021) - Reiter, Aviv; Geiger, Ido
Abstract: This paper asks where Kant stands on the question of the connection between the experience of artistic beauty and moral education, framing this discussion with Batteux's and Schiller's conceptions of this connection. Batteux articulates a cognitivist view of art as engaged with the presentation of morally significant content and draws a direct connection between the experience of art and humanity's moral formation. Kant makes more precise the cognitivist view of art and connects it more closely with morality. We claim that there are interesting connections to be made both with regard to the knowledge that reflection on art affords and with regard to the sort of reflection it demands. Kant, however, does not draw these connections. There are two distinct reasons for this: first, a deep commitment to the idea that moral action is possible for all ordinary rational agents and that it therefore does not require the complex reflection art demands; second, the principled distinction between knowing the laws of morality and actually acting on this knowledge, which stems from the moral–psychological divide between our sensuous and rational natures. Schiller exults the necessary role of art in our moral formation but denies that it stems from the cognitive content of artworks. He rejects the necessity of the divide between our rational and sensuous natures and between knowledge and action. Reconciling our two natures and bringing the human condition into harmony is the role of aesthetic education. We suggest that he can be read as exploiting an unmined vein in Kant's philosophy.